The politics of written language in the Arab world : writing change - Hoigilt, Jacob; Mejdell, Gunvor (Studies in Semitic languages and linguistics, 2017)
The Politics of Written Language in the Arab World connects the fascinating field of contemporary written Arabic with the central sociolinguistic notions of language ideology and diglossia. Focusing on Egypt and Morocco, the authors combine large-scale survey data on language attitudes with in-depth analyses of actual language usage and explicit (and implicit) language ideology. They show that writing practices as well as language attitudes in Egypt and Morocco are far more receptive to vernacular forms than has been assumed. The individual chapters cover a wide variety of media, from books and magazines to blogs and Tweets. A central theme running through the contributions is the social and political function of "doing informality" in a changing public sphere steadily more permeated by written Arabic in a number of media. The e-book version of this publication is available in Open Access